2011
DOI: 10.1155/2011/235354
|View full text |Cite
|
Sign up to set email alerts
|

Gait Disturbances in Dystrophic Hamsters

Abstract: The delta-sarcoglycan-deficient hamster is an excellent model to study muscular dystrophy. Gait disturbances, important clinically, have not been described in this animal model. We applied ventral plane videography (DigiGait) to analyze gait in BIO TO-2 dystrophic and BIO F1B control hamsters walking on a transparent treadmill belt. Stride length was ∼13% shorter (P < .05) in TO-2 hamsters at 9 months of age compared to F1B hamsters. Hindlimb propulsion duration, an indicator of muscle strength, was shorter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Previous studies have suggested that braking and propulsion duration may relate to braking and propulsion ground reaction forces (Hampton et al, 2011; Kale et al, 2004). Similarly, Vrinten and colleagues reported a significant correlation between stance time and von Frey thresholds (R=0.67, p<0.001), the latter of which was strongly correlated with an indirect measure of pressure applied during locomotion using light intensity (R=0.63, p<0.001) (Vrinten and Hamers, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have suggested that braking and propulsion duration may relate to braking and propulsion ground reaction forces (Hampton et al, 2011; Kale et al, 2004). Similarly, Vrinten and colleagues reported a significant correlation between stance time and von Frey thresholds (R=0.67, p<0.001), the latter of which was strongly correlated with an indirect measure of pressure applied during locomotion using light intensity (R=0.63, p<0.001) (Vrinten and Hamers, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with a previous study that did not find significant differences in stance time between rats with or without medial meniscus transection, but did report significant differences in peak vertical and propulsion forces (Allen et al, 2012). Several studies that report changes in temporal parameters following injury only compare to a pre-surgical baseline or uninjured control group, suggesting that these measures are sensitive enough to detect differences above a given functional threshold (Giszter et al, 2008; Hampton et al, 2011; Vrinten and Hamers, 2003). The decreased sensitivity of temporal gait parameters may lead investigators to conclude that there is no effect of a treatment when a difference does indeed exist but cannot be detected (type-II statistical error) (Webb et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cross-validation method, known as leave-one-out (Efron and Tibshirani 1993), was employed to evaluate the performances of the three models and the sensitivity and specificity values of these three models were found to be better than 90%.…”
Section: Methodsmentioning
confidence: 99%